Identifying Key E-Payment Parameters Using the Delphi Method For Recommendation Models in Developing Countries - Ahmed, Saad Mahmood; Mohamed, Ibrahim; Ghaleb, Ebrahim A.A (Journal of Ecohumanism, 2024)
An electronic payment system (EPS) is a technological solution that enables transactions and the purchase of goods and services without the need for physical methods like cash or checks. Small and medium-sized enterprises (Alshamaila et al.) are striving to boost their sales by adopting secure systems such as EPS. EPS is widely considered the foundation of e-commerce, playing a critical role in its growth and expansion .While it is widely acknowledged that designing E--Payment recommendation models depends on parameters linked to e-learning, there remains a lack of consensus on what these parameters precisely entail. This study endeavors to pinpoint the essential parameters for generating E--Payment recommendations, especially within developing countries. Drawing upon pertinent literature, employing the Delphi method, and collaborating with E-- Payment experts, this research identifies ten pivotal e-learning-related parameters. Notably, the findings underscore that among these parameters, "perceived ease of use" stands out as the most critical, while "user preference" emerges as the least influential factor in the realm of e-learning. Based on pertinent literature and employing the Delphi method alongside insights from E-- Payment experts, this paper delineates ten pivotal factors associated with e-learning. The findings underscore that among these parameters, perceived ease of use emerges as the most crucial, while user preference exhibits the least impact on e-learning.